Pengembangan Modul Digital Interaktif Berbasis Cognitive Theory of Multimedia Learning (CTML) dalam Pembelajaran ‘Penalaran Umum’ di Lembaga Kursus dan Pelatihan (LKP) Bintang Pelajar, Bogor - Zainal Abidin; Sigit Wibowo; Rudi Hartono (Jurnal Ragam Pengabdian, 2026)
This study aims to develop an interactive digital module based on the Cognitive Theory of Multimedia Learning (CTML) for teaching general reasoning and to evaluate its feasibility and effectiveness in improving learning outcomes at LKP Bintang Pelajar. The development process adopts a combination of the Dick and Carey model integrated with Borg and Gall, consisting of five stages: initial research and information gathering, planning, product development, feasibility testing, and effectiveness testing. The study involved 90 twelfth-grade students selected through convenience sampling, distributed across various testing phases including one-to-one trials, small group trials, large group trials, and effectiveness testing with treatment and control groups. The results indicate that the developed module is highly feasible for use in learning. Expert evaluations show very high feasibility, with average scores of 4.78 from material experts, 4.35 from media experts, and 4.41 from instructional design experts. Student-based feasibility tests also show positive results, with scores ranging from 4.20 to 4.30, indicating feasible to very feasible categories. Effectiveness testing demonstrates that the module significantly improves learning outcomes. The Wilcoxon test shows a significance value of α = 0.000, with a 39% increase in post-test scores compared to pre-test results. Both treatment and control groups show significant improvements, though the treatment group using the developed module achieved stronger outcomes.